The Effect of Motivation and Organizational Commitment on Turnover Intention with Job Satisfaction as an Intervening Medium (Case Study on Employees of PT Permodalan Nasional Madani Jakarta Branch) - Oktavianti, Ardiana; Safaria, Siti (Formosa Journal of Sustainable Research, 2024)
The aim of this research is to analyze the influence of Motivation on Turnover Intention, to analyze the influence of Organizational Commitment on Turnover Intention, to analyze the influence of Motivation on Job, to analyze the influence of Organizational Commitment on Job Satisfaction, to analyze the influence of Job Satisfaction on Turnover Intention, to analyze the influence of Motivation on Turnover, to analyze the influence of Organizational Commitment on Turnover Intention. Using quantitative, and descriptive research. The respondents are 246 employees of PT PNM. Questionnaires using a Likert scale with the assistance of SmartPLS. The results of this study indicate that motivation has a significant negative effect on turnover intention, organizational commitment has a significant negative effect on turnover intention, motivation has a significant positive effect on job satisfaction, organizational commitment has a significant positive effect on job satisfaction, job satisfaction has a significant negative effect on turnover intention, motivation has a significant negative effect on turnover intention through job satisfaction, and organizational commitment has a significant negative effect on turnover intention through job satisfaction The aim of this research is to analyze the influence of Motivation on Turnover Intention, to analyze the influence of Organizational Commitment on Turnover Intention, to analyze the influence of Motivation on Job, to analyze the influence of Organizational Commitment on Job Satisfaction, to analyze the influence of Job Satisfaction on Turnover Intention, to analyze the influence of Motivation on Turnover, to analyze the influence of Organizational Commitment on Turnover Intention. Using quantitative, and descriptive research. The respondents are 246 employees of PT PNM. Questionnaires using a Likert scale with the assistance of SmartPLS. The results of this study indicate that motivation has a significant negative effect on turnover intention, organizational commitment has a significant negative effect on turnover intention, motivation has a significant positive effect on job satisfaction, organizational commitment has a significant positive effect on job satisfaction, job satisfaction has a significant negative effect on turnover intention, motivation has a significant negative effect on turnover intention through job satisfaction, and organizational commitment has a significant negative effect on turnover intention through job satisfaction